The Impact of Frequency and Duration of Aerobic Dance on Cardiorespiratory Fitness in Adolescent Girls - Poppy Elisano Arfanda; Ians Aprilo; M. Adam Mappaompo; Arimbi; Benny Badaru (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study investigated the effect of aerobic dance frequency and duration on cardiorespiratory fitness in adolescent girls in Makassar. Using a quasi-experimental pre-test and post-test control design, 40 girls aged 17–22 were divided into experimental and control groups (n=20 each). The experimental group performed aerobic dance three times per week for 45–60 minutes over eight weeks, while the control group continued routine activities. Cardiorespiratory fitness was measured using the 12-minute Cooper Test. Data analysis included normality, homogeneity, paired t-tests, and independent t-tests. Results indicated a significant VO₂max improvement in the experimental group (Δ mean = +4.70; p < 0.001) compared to no significant change in the control group (Δ mean = -0.35; p > 0.05). The post-test difference between groups was also significant (t = -3.756; p < 0.001). Regular aerobic dance effectively enhances cardiorespiratory fitness in adolescent girls.